2017
DOI: 10.1515/cclm-2016-0353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EGFR mutations in patients with non-small cell lung cancer by high resolution melting. Comparison with other methods

Abstract: HRM is a good method for mutational screening in EGFR. It is able to detect any change in the sequence of exons 18-21, providing high cost/effectiveness, but samples with low tumor burden may produce false negatives results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It is established that PCR-HRMA has a lower cost and is an accurate tool for mutation scanning, allowing the identification of variations through comparison of HRM curves; consequently, it is used as screening method or for the detection of known hotspot mutations. Its ability in discriminating known mutations is due to the use of reference material, or if this material is not available or novel variations are present in the samples analyzed, the technique is not able to identify the nucleotide change, but only to detect the presence (5456). The HRMA curve shape depends on the number and type of nucleotide changes, with different nucleotide changes yielding different curves.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that PCR-HRMA has a lower cost and is an accurate tool for mutation scanning, allowing the identification of variations through comparison of HRM curves; consequently, it is used as screening method or for the detection of known hotspot mutations. Its ability in discriminating known mutations is due to the use of reference material, or if this material is not available or novel variations are present in the samples analyzed, the technique is not able to identify the nucleotide change, but only to detect the presence (5456). The HRMA curve shape depends on the number and type of nucleotide changes, with different nucleotide changes yielding different curves.…”
Section: Discussionmentioning
confidence: 99%
“…12 EGFR is reported to be overexpressed in 40-80% of NSCLC cases and its mutations in NSCLC are commonly found in people with East Asian ethnicity, adenocarcinoma histological subtype, females and nonsmokers. 11,17 Studies 18,19 have reported that most EGFR mutations occur in exons 18-22 of the tyrosine kinase domains, with the most common mutation being exon 19 deletions and a point mutation in exon 21 (L858R). Furthermore, there are other rare EGFR mutations including substitutions such as glycine 719 with serine, cysteine or alanine in exon 18, which confer sensitivity to EGFR tyrosine kinase inhibitors (TKIs), or mutations associated with resistance to first-generation TKIs such as the T790M mutation in exon 20 or insertions in exon 20.…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…As a result, accurate and sensitive molecular techniques and methods for EGFR T790M mutation analysis are acquired. The current methods for detecting of T790M mutation in clinical practice include real-time PCR assays ( [4]), allele-specific (AS) PCR ( [5]), amplification refractory mutation system (ARMS) ( [1]), droplet digital PCR (ddPCR) ( [1,5]), highresolution melting (HRM) ( [6]), Sanger sequencing ( [6]) and next-generation sequencing (NGS) ( [7]). Among those PCR-based methods, some do not allow to detect low-abundance EGFR T790M mutation, while others are highly sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the limitations in low-abundance mutation detection by use of a critical denaturation temperature (Tc) during PCR amplification. Low-abundance mutation enrichment by use of COLD-PCR has been demonstrated in combination with several downstream approaches such as TaqMan-based real-time PCR ( [16]), HRM ( [17]), Sanger sequencing ( [6]) and pyrosequencing ( [14]). When combined with pyrosequencing, COLD-PCR can improve mutation detection and identification by approximately 5-fold to 35-fold ( [14]).…”
Section: Introductionmentioning
confidence: 99%